Code of the City of Selma 96, ch. 7, § 275 (1862) - (:unkn) unknown (My University, 1862)
Any person who carries concealed about his person a loaded pistol or other kind of firearm, a bowie knife, dagger, or knife of like kind, unless threatened with, or having reason to apprehend an attack, or being upon or about to start upon a journey, shall upon conviction be fined not less than ten dollars, one half of which goes to the informer, when collected.
Keywords: CARRY - CONCEALED